El asedio al Raval: una aproximación al pasado y presente de las transformaciones urbanísticas del barrio barcelonés - Fernández Gras, Miquel (Oñati Socio-Legal Series, 2011)
The incisions perpetrated in Barcelona’s Public Space have been justified with the discourse of the need to put Barcelona into the market of the Global Cities. In these cities the production of profits is deputized at the service sector in prejudice of the industrial itself and it promotes the enormous entrance of property, financial and tourist capital. We came across a process of tertiarization which, in due time, requires a musealization of the city that makes it attractive for financial investors. These transformations -recognized under Barcelona's Model label -do not attempt only to modify the physical morphology of the city, rather, they aspire to transform their inhabitants' cultural and commodities practices to the point, if it is precise, to substitute the same neighbours for other ones further in harmony with these new scenes, in what is known as Gentrification. Assuming that this substitution of habits and of inhabitants has not taken place naturally, the Town council, negotiating various types of public and private interests has established a normative disposed frame to the aesthetic and ethical renewal. It has to do with a new set of standards that narrow the variety of ways of behaving in the Public Space. They specially affect any subject that does not respond to a sort of universal standard rules of behaviour. This regulation brought together in November 2005, is popularly known as “Ordenança cívica”. The ethnography of Robadors's street of Barcelona (Catalunya), allows problematizing Public Space concept and contrasting it to Multitude with the intention of exposing the existent correlations between these urban transformations and the interested conceptualization of public space notion.